2020
DOI: 10.3390/ijms21155330
|View full text |Cite
|
Sign up to set email alerts
|

ALIAmides Update: Palmitoylethanolamide and Its Formulations on Management of Peripheral Neuropathic Pain

Abstract: Neuropathic pain results from lesions or diseases of the somatosensory nervous system and it remains largely difficult to treat. Peripheral neuropathic pain originates from injury to the peripheral nervous system (PNS) and manifests as a series of symptoms and complications, including allodynia and hyperalgesia. The aim of this review is to discuss a novel approach on neuropathic pain management, which is based on the knowledge of processes that underlie the development of peripheral neuropathic pain; in parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 225 publications
(253 reference statements)
0
42
0
1
Order By: Relevance
“…Although the mechanism of action of PEA is not yet well defined, it is well known that PEA was able to inhibit mast cell degranulation, through an Autacoid Local Injury Antagonism. At the basis of the several hypotheses advanced over the years on the mechanism of action of PEA, there is the capability to inhibit NF-kβ translocation into the nucleus, not directly but through a bind with receptor like PPARα [ 51 ]. As a result, treatment with um-PEA efficaciously blocked the phosphorylations of IκBα, NF-κB, which suggested that um-PEA suppressed excessive cytokine production by inhibiting NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action of PEA is not yet well defined, it is well known that PEA was able to inhibit mast cell degranulation, through an Autacoid Local Injury Antagonism. At the basis of the several hypotheses advanced over the years on the mechanism of action of PEA, there is the capability to inhibit NF-kβ translocation into the nucleus, not directly but through a bind with receptor like PPARα [ 51 ]. As a result, treatment with um-PEA efficaciously blocked the phosphorylations of IκBα, NF-κB, which suggested that um-PEA suppressed excessive cytokine production by inhibiting NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although therapeutic alternatives in MCAD patients with pain are drugs that profoundly stabilize MCs, it remains a challenge considering its adverse effects on human beings (Wirz and Molderings, 2017 ). Based on the demonstrated efficacy in pain, analgesics that can significantly mitigate MC degranulation, such as morphine (Vincent et al, 2016 ), Palmitoylethanolamide (D’Amico and Impellizzeri, 2020 ), and ketotifen (Klooker et al, 2010 ), are promising for treating all those painful conditions in which MC activation is the main cause. Pharmacological targeting of MC proliferation, specific surface antigens, and downstream signaling pathways, in addition to stabilizing MCs, may improve analgesics therapy (Molderings et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical trials, it has been observed that agonists of CB2 receptor exert an anti-inflammatory effect, which might be potentially beneficial in chronic pain states [78]. In turn, in preclinical and clinical settings OR agonists such as morphine or fentanyl exerts immunosuppressive effect, resulting in reduction of either macrophage numbers or production of macrophage proinflammatory cytokines [79] Potentially, immune cells involved in peripheral neurogenic inflammation and their receptors may be target for topically applied cannabinoids or opioids [80][81][82]. Immune cells express GABA receptors and GABA as well.…”
Section: Role Of Immunocompetent Cells In Peripheral Mechanisms Of Npmentioning
confidence: 99%
“…In the periphery, CB1 receptors are expressed on nociceptive nerve endings and the DRG, whereas CB2 receptors are located in immune cells and keratinocytes [78,172]. Either CB1 or CB2 receptors may be targeted by cannabinoids administered topically, evoking analgesic effect in both inflammatory and neuropathic pain [78,81,[98][99][100]172].…”
Section: Treatments Acting On Cannabinoid Receptorsmentioning
confidence: 99%